A case of diprosopus in a Friesian calf - Μενεγάτος, Ι.; Ζώλος, Α.; Ξυλούρη, Ε.; Πανοπούλου, Ε.; Παπαντωνάκης, Κ.; Στοφόρος, Ε. (Journal of the Hellenic Veterinary Medical Society, 2019)
It is described a case of a diprosopus Friesian calf that was born by a multiparus cow. The two heads had four eyes and two ears. They were conjoined to cheaks. The dimensions of the two heads presented small differences. Differences also existed between the whorls of the heads, the shape and the area of the stars, as well as the impints of the muzzles. Also the diprosopus had unilateral brachygnathia inferior and grom the non cranial malformations had arthrogryposis of the legs. This case of malformation in cattle consists the frequent of conjoined twins. It has been observed that the frequency of occurence of diprosopus calves are 8 every 100.000 cows